Hadith of Ghadir Khum and the Framing of Shia Teachings: A Comparative Analysis of Panjimas.com and ShiahIndondesia.com from Robert M. Entman’s Perspective - Nur Annisa Istifarin; Muhid Muhid (Diroyah : Jurnal Studi Ilmu Hadis, 2026)
The theological divergence between Sunni and Shia interpretations of the Hadith of Ghadir Khum remains a persistent issue in Islamic discourse, particularly within the digital sphere. This study aims to analyze how two online Islamic media portals, Panjimas.com and ShiahIndonesia.com, frame the Ghadir Khum event and its implications for leadership in Islam. The research applies Robert M. Entman's framing model, encompassing four elements: define problems, diagnose causes, make moral judgment, and treatment recommendation. The findings reveal that Panjimas.com frames the Hadith of Ghadir Khum as a theological misinterpretation by the Shia that requires correction. It emphasizes the term mawla as meaning "helper" rather than "leader," thus taking a delegitimizing stance toward Shia claims of imamate. Conversely, ShiahIndonesia.com employs an affirmative framing, interpreting Ghadir Khum as a spiritual and social declaration of Ali bin Abi Thalib's leadership and as a continuation of prophetic authority within the doctrine of imamate. Consequently, both media represent contrasting ideological orientations: Panjimas.com upholds Sunni orthodoxy through a discourse of rejection, while ShiahIndonesia.com reinforces Shia identity through a discourse of affirmation. These differing frames demonstrate that the Hadith of Ghadir Khum functions not merely as a religious text but as a symbolic arena of meaning and authority contestation within the contemporary Islamic digital public sphere.